Pengaruh Senam Prolanis Terhadap Penurunan Kadar Glukosa Darah Sewaktu Pasien Diabetes Mellitus Tipe 2 di Puskesmas Oepoi - Appolonaris Tomas Berkanis; Erna Febriyanti; Zarah Eunike Riwu Lay (Universitas Insan Budi Utomo, 2026)
Type 2 diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin function. One non-pharmacological management effort to control blood glucose levels is Prolanis Gymnastics. This study aimed to determine the effect of Prolanis Gymnastics on reducing random blood glucose levels in patients with type 2 diabetes mellitus at the Oepoi Public Health Center. This study employed a quantitative, quasi-experimental design with a pre-test post-test control group approach. This research was conducted from March 15 to April 11, 2026. The sample consisted of 40 respondents who met the inclusion criteria: 1. Type 2 DM patients registered at the Oepoi Community Health Center; 2. Patients still able to perform light to moderate physical activity, particularly Prolanis exercises (not in a worsening condition such as pressure ulcers); 3. Willingness to participate in the study by signing an informed consent. The sample consisted of 40 respondents,divided equally between intervention and control groups (20 respondents each), selected through a total sampling technique. Blood glucose levels were measured before and after the intervention using a glucometer. Data were analyzed using the Shapiro-Wilk test, Paired Sample t-Test, and Mann-Whitney U Test. The mean blood glucose level in the intervention group decreased from 168.85 ± 11.79 mg/dL to 153.75 ± 10.40 mg/dL, with a mean reduction of 15.10 mg/dL (p < 0.001). In the control group, the mean blood glucose level decreased from 182.35 ± 14.60 mg/dL to 179.60 ± 14.63 mg/dL (p < 0.001). The Mann-Whitney U Test showed a significant difference in blood glucose levels between the intervention and control groups (Z = -4.895; p < 0.001).Prolanis Gymnastics significantly reduces blood glucose levels in patients with type 2 diabetes mellitus and serves as an effective non-pharmacological intervention in primary health care.